2010
DOI: 10.1590/s0100-69912010000500008
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos dos ácidos graxos sobre a regeneração hepática em ratos

Abstract: Omega-3 PUFA retarded post-PH liver regeneration, probably through inhibition of oxidative stress. Omega-6 PUFA increased TBARS concentrations in blood and liver but did not alter the evolution of the liver regenerative process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Another study dealing with Ω3FAs supplementation, which did not use a regeneration model, reported that this compound did protect against oxidative stress induced DNA-damage in the liver [7]. However, there are contradicting studies reporting negative effects of long chain Ω3FAs on regenerating [26] and normal liver [27] with diverse results on oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Another study dealing with Ω3FAs supplementation, which did not use a regeneration model, reported that this compound did protect against oxidative stress induced DNA-damage in the liver [7]. However, there are contradicting studies reporting negative effects of long chain Ω3FAs on regenerating [26] and normal liver [27] with diverse results on oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning these previous reports and these results (which demonstrated the efficacy of DKT to the liver), we hypothesized that DKT may accelerate liver regeneration after hepatectomy. A 70% hepatectomy rat model was established according to the classical Higgins-Anderson procedure [13] , and the model was then gavaged with DKT every 12 h from 12 h before the laparotomy to 72 h after the laparotomy. The liver/body weight ratio and number of Ki67 positive cells were compared between the DKT group and control group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is known that corn oil has significant levels of omega-6 and some studies suggest that diets rich in omega-6 provided improvement in liver regeneration 20 . Thus, we included this oil to evaluate if this substance shows improvement liver regeneration or if it is a standard of control substance to experiments with copaiba.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the measurement of alkaline phosphatase and ɤ GT (Table 2), no significant difference between groups was showed. Regarding total bilirubin and fractions (Table 3) injury attenuation by copaiba oil was not due to stimulation of liver regeneration 9,11,20 . This evidence suggest the hypothesis that Copaiba`s mechanism takes place reducing free radicals in tissue by herbal anti-inflammatory properties, previously described by Noguchi et al 15 , suggesting an actual hepato protective effect of this oil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation